Effects of Xiaoshuan Enteric-Coated Capsule on White and Gray Matter Injury Evaluated by Diffusion Tensor Imaging in Ischemic Stroke. Issue 6 (June 2019) - Zhang, Jian; Chen, Shengpan; Shi, Weilong; Li, Manzhong; Zhan, Yu; Yang, Le; Zou, Haiyan; Lei, Jianfeng; Chai, Xinlou; Gao, Kuo; Liu, Junjie; Wang, Wei; et al.
Xiaoshuan enteric-coated capsule (XSECC) is a drug approved by the Chinese State Food and Drug Administration for the treatment of stroke. This study was to investigate the effects of XSECC on white and gray matter injury in a rat model of ischemic stroke by diffusion tensor imaging (DTI) and histopathological analyses. The ischemia was induced by middle cerebral artery occlusion (MCAO). The cerebral blood flow measured by arterial spin labeling was improved by treatment with XSECC on the 3rd, 7th, 14th and 30th days after MCAO. Spatiotemporal white and gray matter changes in MCAO rats were examined with DTI-derived parameters (fractional anisotropy, FA; apparent diffusion coefficient, ADC; axial diffusivity, λ// ; radial diffusivity, λ⊥ ). The increased FA was found in the XSECC treatment group in the corpus callosum, external capsule and internal capsule, linked with the decreased λ//, λ⊥ and ADC on the 3rd day and reduced ADC on the 30th day in the external capsule, suggesting XSECC reduced the axon and myelin damage in white matter after stroke. The relative FA in the striatum, cortex and thalamus in XSECC treatment group was significantly increased on the 3rd, 7th, 14th and 30th days accompanied by the increased λ// on the 3rd day and reduced relative ADC and λ⊥ on the 30th day, indicating that XSECC attenuated cell swelling and membrane damage in the early stage and tissue liquefaction necrosis in the late stage in gray matter after stroke. Additionally, XSECC-treated rats exhibited increased mean fiber length assessed by diffusion tensor tractography. Moreover, histopathological analyses provided evidence that XSECC relieved nerve cell and myelin damage in white and gray matter after stroke. Our research reveals that XSECC could alleviate white and gray matter injury, especially reducing nerve cell damage and promoting the repair of axon and myelin after ischemic stroke.